The Power of the Capability Constraint: On Russia’s Strength in the Arctic Territorial Dispute - Valko Irina (Sciendo, 2016)
Based on a geographical-administrative definition of the region, the theoretical assumptions of contemporary French structuralist geopolitics, cross-sectional data for 1990, 1995, 2000, 2005 and 2010 from the Updated Arctic Regional Attributes Dataset, and the technical capabilities of MS Office Excel 2010, this research (a) reveals and contrasts the Arctic states’ capability constraints deriving from their longitudinal material and virtual power potential (physical potential, socio-economic potential, military potential, and symbolic potential); and (b) analyses the role of this constraint in the process of preference formation in case of one specific Arctic actor, Russia, in the Arctic territorial dispute. This study confirms that Russia’s capability constraint is the lowest in the region and that the latter does not form a stable trend throughout the period studied. It also suggests the preference formation framework for Russia in the Arctic dispute based on the evolution of its polar capability constraint.